The fingerprints of weathering: Grain size distribution changes along weathering sequences in different lithologies - Román-Sánchez, Andrea; Temme, Arnaud; Willgoose, Garry; van den Berg, Denys; Gura, Colleen M.; Vanwalleghem, Tom (Geoderma, 2021)
•Results from vertical size distribution are confronted with a fragmentation model.•Lithology is an important determinant of the rock fragmentation mechanism.•Results show well fit with most of the rock fragmentation models used. The weathering mechanisms that cause fragmentation of particles in the transition from bedrock to saprolite and regolith are little known. Yet, their quantification is an important missing link in the development of critical zones. To provide observational underpinning of mechanistic inference, we sampled and analysed the vertically changing particle size distribution in weathering profiles of varying lithology: quartzite, schist, gneiss and shale. The samples were studied for mineral composition by X-ray powder diffraction (XRD) and assessed whether these were consistent with the field identification. Then, simulations from twelve theoretical particle fragmentation models were confronted to the vertical particle size distribution measured. The models simulate different particle-size implications of physical and chemical weathering, but do not include surface effects on particle size distribution such as armouring. The results demonstrate that the lithology is an important determinant of the rock fragmentation mechanism. Furthermore, it is shown that the rock fragmentation models used here are a useful tool to identify geomorphological processes as soil redistribution or amouring. Further research will need to generate more data on weathering sequences in different environments.